O Estado organizacional dos grandes escritórios de advocacia do Brasil: dois estudos de caso - Hapner, Paulo Afonso Manfredini (2002)
The objective of this study was to identify the real organizational status of major law firms in Brazil compared to fordism and post-fordism organizational economic paradigms. In order to fulfill the objectives, an exploratory-explanatory research was carried out through case studies. The two major Brazilian law firms, according the study developed by the newspaper Gazeta Mercantil (PANORAMA SETORIAL ¿ ESCRITÓRIOS DE ADVOCACIA, 2002), Pinheiro Neto Advogados (PN) and Tozzini, Freire, Teixeira e Silva Advogados (TFTS), were researched. The case study was based on multiple evidence analysis: semi-structured interviews, documents and records analysis, and direct observations. The report of the research was structured by presenting a detailed introduction about lawyer and the law firms, including their historics main characteristics and factors which lead up to the constitution of these firms, showing the relationship among information technologies, globalizations and the need of strategic recontextualization of law firms. The data collected showed how these aspects presented in the studied unities. It was concluded through this research that PN and TFTS present an organizational development compatible to what is frequently practised in the organizations as far as contemporary organizational techniques and tools are concerned; neither fordism nor the transitional process to post-fordism, intensified the division of work of the lawyer; the new information technologies are essential for the maintenance of the sustained competitive advantage within the post-fordism scenario.